“In the World of Iron and Steel”: On the Ethnography of work, unemployment and hope - Potkonjak, Sanja; Škokić, Tea (2013)
crisis, as well as the transitional crisis that preceded it, and is illustrated on the example of the devastation of the Sisak Ironworks. The collapse of the Croatian industry is explained primarily as a bankruptcy of political, ideological and economic values from the socialist period and only secondarily as the result of the global economic crisis. The second set of issues is revealed in the interviews with the employees of the Sisak Ironworks who were laid off, whose narratives mostly conceptualize their life without work, who talk about their life while they were still employed, and who consider their future life and work. In all these interviews the word “hope” is repeated as a kind of a leitmotif. The notion of hope is, in fact, the object of the final set of issues. In recent years, within the humanities and social sciences, the concept of “hope” was given considerable importance in research, especially in the analysis of individual and collective traumatic experience, such as losing one’s job. Thus, the authors present some of the more important theoretical articles about hope, and problematize them based on their own field notes.
ENG